AUDIT OPERASIONAL PEMASARAN TERHADAP PERSPEKTIF KEPUASAN PELANGGAN ATAS PRODUK NU GREEN TEA PT ABC PRESIDENT INDONESIA - Widia Praptiwi, SE., Ak., M.Ak. , CA.; Dwi Richi Julian (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
The purpose of this research is to find out customer satisfaction of Nu Green Tea drinks through marketing programs and marketing budgets. As Marketing operational audit can use not only financial data as a key performance indicator. Data obtained by distributing questionnaires to several customers, namely traditional shops or agents that have been determined. The analysis used descriptive analysis method with describe quantitative analysis approach or describe the object of research to find out how effective and efficient the marketing program is on the marketing budget. Among of the results show that Marketing programs and marketing budgets simultaneously have a positive and significant impact on customer satisfaction. Marketing programs are influenced by the existence of programs that include the development of human resources on the internal part, including marketing training. Marketing training, among the others, is to improve quality in order to improve the best sales performance by selling effectively and productively. Identifying the target market will help in developing an effective marketing strategy. Introducing products to consumers, promoting consistently, continuously, and in creative ways. Internet marketing is one of marketing strategy that is very effective, knowing the tastes of customers and customer needs by placing on social networking sites.